Pengembangan Karakter Remaja Melalui Kegiatan Bible Camp di GGP Sanggbuana: Sebuah Inisiatif Pengabdian Masyarakat - Lasmauli Gurning; Maria Titik Windarti (LPPM - STT Kadesi Bogor, 2024)
Bible Camp activities have emerged as one of the effective methods in adolescent character development, particularly in the context of introducing religious and moral values. This research aims to describe and analyze the impacts of Bible Camp activities as a community service initiative on adolescent character development in GGP Sanggbuana. Data collection methods were conducted through participatory observation, interviews, and documentary studies. The research findings indicate that Bible Camp activities are capable of positively contributing to adolescent character formation through the dissemination of moral and religious values, the development of social skills, and the reinforcement of community bonds. The implications of these findings underscore the need to continually promote and develop similar activities as part of community service efforts to strengthen adolescent character at the local level.